Life expectancy among HIV-positive patients in Rwanda: a retrospective observational cohort study. Issue 3 (March 2015) - Nsanzimana, Sabin; Remera, Eric; Kanters, Steve; Chan, Keith; Forrest, Jamie I; Ford, Nathan; Condo, Jeanine; Binagwaho, Agnes; Mills, Edward J
Summary: Background: Rwanda has achieved substantial progress in scaling up of antiretroviral therapy. We aimed to assess the effect of increased access to antiretroviral therapy on life expectancy among HIV-positive patients in two distinct periods of lower and higher antiretroviral therapy coverage (1997–2007 and 2008–11). Methods: In a retrospective observational cohort study, we collected clinical and demographic data for all HIV-positive patients enrolled in care at 110 health facilities across all five provinces of Rwanda. We included patients aged 15 years or older with a known enrolment date between 1997 and 2014. We constructed abridged life tables from age-specific mortality rates and life expectancy stratified by sex, CD4 cell count, and WHO disease stage at enrolment in care and initiation of antiretroviral therapy. Findings: We included 72 061 patients in this study, contributing 213 983 person-years of follow-up. The crude mortality rate was 33·4 deaths per 1000 person-years (95% CI 32·7–34·2). Life expectancy for the overall cohort was 25·6 additional years (95% CI 25·1–26·1) at 20 years of age and 23·3 additional years (95% CI 22·9–23·7) at 35 years of age. Life expectancy at 20 years of age in the period of 1997–2007 was 20·4 additional years (95% CI 19·5–21·3); for the period of 2008–11, life expectancy had increased to 25·6 additional years (95% CI 24·8–26·4). Individuals enrolling in care with CD4 cell counts of 500 cells per μL or more, and with WHO disease stage I, had the highest life expectancies. Interpretation: This study adds to the growing body of evidence showing the benefit to HIV-positive patients of early enrolment in care and initiation of antiretroviral therapy. Funding: Bill & Melinda Gates Foundation .